OPTIMALISASI PENGGUNAAN APLIKASI PLN MOBILE UNTUK MENINGKATKAN KEPUASAN PELANGGAN TERHADAP PELAYANAN KELISTRIKAN PADA PT. PLN UNIT INDUK DISTRIBUSI BALI: Optimizing the Use of the PLN Mobile Application To Increase Customer Satisfaction With Electricity Services at PT. PLN Bali Main Distribution Unit - Yadnya, Sang Ayu Made Cintika; Dewi, Kadek Cahya; Susanti, Leni Anggraini (Ganec Swara, 2025)
Technological advances have brought various innovations that simplify daily life, including electricity services. PT PLN (Persero) responded to this by developing the PLN Mobile application to improve customer satisfaction, particularly at PT PLN Bali Distribution Unit. This study aims to identify factors that hinder the performance of PLN Mobile, analyze the impact of its use on efforts to improve customer satisfaction, and formulate service optimization strategies. The study was conducted over six months in the commerce subsection of customer service using descriptive and qualitative descriptive statistical analysis methods. Data collection techniques included observation, interviews, documentation, and questionnaire distribution. Assessments were conducted on four indicators of PLN Mobile usage and four indicators of customer satisfaction. The results indicate that although the service is generally running well, there are still several indicators that are not optimal due to recurring internal and external constraints. Therefore, it is recommended to collect feedback from users to improve service quality. Optimization efforts are carried out by considering the needs, desires, expectations, and perceptions of users to align with the company's goals, vision, and mission.